1991
DOI: 10.1002/1097-0142(19910215)67:4<990::aid-cncr2820670422>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the macrophage colony-stimulating factor and its receptor in gynecologic malignancies

Abstract: Recently, hematopoietic growth factors have been implicated in protean nonhematopoietic processes. In the current study, expression of macrophage colony-stimulating factor (M-CSF) and its receptor (the c-fms proto-oncogene) was investigated in 42 samples of gynecologic tissues. There were 15 samples of normal ovarian and uterine tissue or benign conditions of these organs; 11 samples of primary ovarian cancer tissue; seven samples of metastatic ovarian cancer tissue; and nine samples of primary endometrial can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
51
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(51 citation statements)
references
References 22 publications
0
51
0
Order By: Relevance
“…Abnormally high CSF1R expression has been associated with aggressive behavior and poor outcome in a variety of malignancies, including breast, 22,23 endometrial, 24,25 ovarian, 26,27 and prostate cancers. 28 The follow-up time in this series is still relatively short to allow a meaningful evaluation of the prognostic value of CSF1R overexpression in renal cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abnormally high CSF1R expression has been associated with aggressive behavior and poor outcome in a variety of malignancies, including breast, 22,23 endometrial, 24,25 ovarian, 26,27 and prostate cancers. 28 The follow-up time in this series is still relatively short to allow a meaningful evaluation of the prognostic value of CSF1R overexpression in renal cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 Concomitant expression of CSF1R and CSF1 was also observed in endometrial cancer cells and it is absent in the adjacent normal tissue. 24,25 Finally, it has been shown in uterine cervical carcinomas that the CSF1/CSF1R-signaling pathway is involved in enhanced survival and invasion of cancer cells via an autocrine mechanism. 30 Our finding of increased CSF1R expression at both the mRNA and protein level in most clear cell renal cell carcinomas suggests that tumor cells may be hypersensitive even to normal CSF1 levels, presumably resulting in decreased apoptosis and increased ability to invade.…”
Section: Discussionmentioning
confidence: 99%
“…Our observation was largely based on the RT-PCR technique, and positive RT-PCR does not mean substantial existence of proteins. Frequent co-expression of these transcripts in ovarian carcinomas, however, has been reported by other investigators (Baiocchi et al, 1991;Bauknecht et al, 1994). Taken together, it is conceivable that autocrine regulation of M-CSF may exist in some ovarian epithelial carcinomas.…”
Section: Discussionmentioning
confidence: 80%
“…It is produced by fibroblasts and endothelial cells. In addition, some kinds of carcinoma, such as ovarian epithelial carcinomas, endometrial carcinomas and mammary carcinomas, have been shown to produce M-CSF (Baiocchi et al, 1991). An abnormally high level of M-CSF is found in the sera of ovarian epithelial carcinoma patients with active disease, and the usefulness of M-CSF as a tumour marker in ovarian epithelial carcinoma has been proposed (Kacinski et al, 1989;Suzuki et al, 1993).…”
mentioning
confidence: 99%
See 1 more Smart Citation